2014
DOI: 10.1007/s00221-014-4018-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric balance control between legs for quiet but not for perturbed stance

Abstract: Interlateral performance asymmetry in upright balance control was evaluated in this investigation by comparing unipedal stance on the right versus the left leg. Participants were healthy young adults, hand-foot congruent preference for the right body side. Balance performance was evaluated in unperturbed quiet stance and in the recovery of balance stability following a mechanical perturbation induced by unexpected load release. Evaluation was made under availability of full sensory information, and under depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
4
14
0
4
Order By: Relevance
“…Clinically this suggests that, for healthy adults, there is an anterior shift of COG in SLS tests. This result agrees with the significant findings in the study by Teranishi with the right foot (Clifford & Holder-Powell, 2010) and greater stability in right SLS compared with the left (Vieira et al, 2014). This may have implications for gait performance particularly in patients who have had a stroke.…”
Section: Changes Evident With Altered Base Of Support Configuration (supporting
confidence: 83%
See 4 more Smart Citations
“…Clinically this suggests that, for healthy adults, there is an anterior shift of COG in SLS tests. This result agrees with the significant findings in the study by Teranishi with the right foot (Clifford & Holder-Powell, 2010) and greater stability in right SLS compared with the left (Vieira et al, 2014). This may have implications for gait performance particularly in patients who have had a stroke.…”
Section: Changes Evident With Altered Base Of Support Configuration (supporting
confidence: 83%
“…In RSLS the proportions were very similar for each of the three age groups (92-97%). This does seem to agree with Vieira et al (2014) who found, in young adults, greater stability for stance on the dominant lower limb. If, as Nichols et al (1995) have suggested, an anterior shift occurs to position the COG closer to the centre of the BOS to increase the distance of the COG from the BOS boundaries and enhance stability, the greater proportions of anterior location in the LSLS for the young and middle groups may indicate less confidence in control for stance on the non-dominant foot and therefore a need to be closer to the centre of the BOS.…”
Section: Centre Of Gravity Location As Age Increases (Studies 3 and 4supporting
confidence: 59%
See 3 more Smart Citations